Book review: The Architecture of Demas Nwoko, by John Godwin and Gillian Hopwood - le Roux, Hannah (Farafina, Lagos, 2007)
Given the challenges of access and archives, it is hard to get down to detail in the documentation of modern African architecture. This architectural monograph by Nigerian based architects John Godwin and Gillian Hopwood is a moving and meticulous catalogue of the designed work of their friend, the artist Demas Nwoko, that is refreshingly full of both architectural and anecdotal details. It begins with two short essays on Nwoko’s creative background and an analysis of his approach to design, but for the most part describes, in drawings, text and photographs, his twelve built and five unexecuted works.
Book review by Hannah le Roux
Keywords: Book review, Demas Nwoko, John Godwin and Gillian Hopwood.